APLIKASI SISTEM INVENTARIS BARANG PADA KANTOR CAMAT AIKMEL - Pujiwalida, Isinaning; Ismiyarti, Wilia; -, Ekastini; Dzil Ikram, Fadhli; Nuryadi, Halid; Hadi, Mukhtar; Robbani, Farisan; Balafif, Sabri; -, Yuliadi (Fakultas Teknologi dan Ilmu Komputer Universitas Prima Indonesia, 2024)
The development of information technology and the digital world is currently very rapid in all fields that can help humans complete various activities. With computer technology, all human data processing and storage activities become very easy, fast, and automatic. The Aikmel Sub-District Office, in managing inventory of goods, still uses manual methods, making it troublesome for employees to recap data on goods as assets. In this study, the development of the Goods Inventory Information System application by the functional requirements that facilitate employees of the Aikmel Sub-District Office in managing the data of goods. Applications were developed using the Extreme Programming (XP) method and MySQL database with Xampp service. This application can facilitate inventory data management and record incoming and outgoing goods. In addition, employees can easily recap data on incoming and outgoing goods quickly and automatically.